Eustachian Tube Dysfunction–Related Symptoms in Chronic Nasal Obstruction Caused by Inferior Turbinate Enlargement. (December 2017) - Harju, Teemu; Kivekäs, Ilkka; Numminen, Jura; Rautiainen, Markus
Objective: The aim of this study was to evaluate the relationship between chronic nasal obstruction caused by inferior turbinate enlargement and Eustachian tube dysfunction–related symptoms using the Eustachian Tube Dysfunction Questionnaire (ETDQ-7) as an assessment method. Methods: A total of 80 adults were enrolled. Group 1 comprised consecutive patients with enlarged inferior turbinates and group 2 comprised healthy controls. The ETDQ-7 scores and tympanometry results of both groups were analyzed and compared. Results: The median total scores of the ETDQ-7 in groups 1 and 2 were 1.9 (interquartile range, 1.4-2.8) and 1.1 (interquartile range, 1.0-1.7), respectively ( P < .001). There was no significant difference in the abnormal tympanometry results between the groups. There was no significant difference in the ETDQ-7 total score between the patients with allergic sensitization and other patients in group 1. Conclusions: Patients with inferior turbinate enlargement have more symptoms related to Eustachian tube dysfunction than healthy controls. Most patients with Eustachian tube dysfunction had normal tympanometry and normal otoscopy, which indicates a baro-challenge-induced Eustachian tube dysfunction. Whether the patient has allergic sensitization or not does not seem to cause a difference in symptoms related to Eustachian tube dysfunction.